2016
DOI: 10.1097/psy.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Facial Emotion Processing in Patients With Dissociative Seizures

Abstract: Recognition accuracy, emotional intensity judgements, skin conductance levels (SCLs) and responses (SCRs) were dependent measures.Analyses controlled for a range of potentially confounding variables, including anxiety, depression and medication effects. Results:The DS group were less accurate at identifying facial expressions than

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…Reduced accuracy for recognising emotional facial expressions and reduced phasic skin conductance responses (SCRs) was observed in FND-seiz participants in one study 15. Altered reaction times for explicit identification of sad and happy faces have also been reported in children and adolescents with FND,32 alongside elevated heart rate (HR) and reduced heart rate variability (HRV) in the same sample 33.…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Reduced accuracy for recognising emotional facial expressions and reduced phasic skin conductance responses (SCRs) was observed in FND-seiz participants in one study 15. Altered reaction times for explicit identification of sad and happy faces have also been reported in children and adolescents with FND,32 alongside elevated heart rate (HR) and reduced heart rate variability (HRV) in the same sample 33.…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 96%
“…Findings include elevated salivary cortisol,34 HR,33 skin conductance levels,15 SCRs41 and lower HRV 27 33 42. In addition, potentiated startle responses have been observed in patients with FND-movt 43…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 99%
“…All methods for acquiring, extracting, and reducing the SC variables followed recommended guidelines (Boucsein et al, 2012;Dawson, Schell, & Filion, 2000); the methods were described in full previously (Pick et al, 2016) and can be found in Data S3. Baseline SCLs were calculated from the average values obtained across the resting habituation period prior to the experiment, whereas task SCLs were calculated from the average of the values obtained during the last 5-s of each ISI in the experimental task (i.e., at rest, fixating on a single cross-hair).…”
Section: Skin Conductance Datamentioning
confidence: 99%
“…There is now substantial experimental evidence that people with DS display alterations in responsivity to social emotional stimuli, characterized by increased cognitive interference by and behavioural avoidance of emotional facial expressions (Bakvis et al, 2009;Bakvis, Spinhoven, Putman, Zitman, & Roelofs, 2010;Bakvis, Spinhoven, Zitman, & Roelofs, 2011;Gul and Ahmad, 2014) as well as deficits in 'theory of mind' (Sch€ onenberg et al, 2015) and explicit facial expression recognition (Pick, Mellers, & Goldstein, 2016). However, less is known about how people with DS respond to other, more general emotional stimuli.…”
mentioning
confidence: 99%
“…Additionally, a limited number of experimental studies have indicated abnormalities in emotional processing in patients with DS, most commonly in responses to facial affect. Findings include impaired switching from a facial emotion categorisation task [31], exaggerated interference by facial emotion on working memory performance [37], and reduced explicit recognition and attenuated autonomic responses to facial expressions relative to controls [38]. The first experimental study of this nature [39] reported an increased attentional bias towards angry faces in patients with DS (n = 19) compared to healthy controls (n = 20) (p < .05), on an emotional Stroop test involving preconscious processing of affectively valenced facial stimuli.…”
Section: Introductionmentioning
confidence: 99%